e-banking Services and Customer Satisfaction with reference to Nepalese Banking Sector - Makshindra Thapa, (Journal of Business and Social Sciences, 2023)
This study is intended to investigate the impact of e-banking services on customer satisfaction, as this area of research is still in the foundation phase in Nepal. The conceptual framework included five e-banking service dimensions: ease of use, efficiency, reliability, responsiveness, and security as predictors and customer satisfaction as dependent variables. The descriptive and casual-comparative research was conducted with a sample of 232 bank customers actively using e-banking services. A questionnaire survey was an instrument to collect data, and along with descriptive and correlation analysis, the regression analysis was conducted with the use of SPSS and JASP. The empirical result shows a positive and significant impact of e-banking service dimensions on customer satisfaction. The findings show that ease of use, security, efficiency, and reliability have a relatively greater impact on customer satisfaction. However, responsiveness has a weak impact on customer satisfaction. E-banking is an inevitable part of the modern banking system that enhances customer satisfaction and core competencies in the area and provides competitiveness. The banking institutions can focus on maximizing firm value through customer satisfaction, retention, and loyalty through the best e-banking services.